Establishment of a Novel Fetal Growth Restriction Model and Development of a Stem-Cell Therapy Using Umbilical Cord-Derived Mesenchymal Stromal Cells - Kitase, Yuma; Sato, Yoshiaki; Arai, Sakiko; Onoda, Atsuto; Ueda, Kazuto; Go, Shoji; Mimatsu, Haruka; Jabary, Mahboba; Suzuki, Toshihiko; Ito, Miharu; Saito, Akiko; Hirakawa, Akihiro; et al. (Frontiers in Cellular Neuroscience, 2020)
Fetal growth restriction (FGR) is a major complication of prenatal ischemic/hypoxic exposure and affects 5%–10% of pregnancies. It causes various disorders, including neurodevelopmental disabilities due to chronic hypoxia, circulatory failure, and malnutrition via the placenta, and there is no established treatment. Therefore, the development of treatments is an urgent task. Our aim was to develop a new FGR rat model with a gradual restrictive load of uterus/placental blood flow and to evaluate the treatment effect of the administration of umbilical cord-derived mesenchymal stromal cells (UC-MSCs). To create the FGR rat model, we used ameroid constrictors that had titanium on the outer wall and were composed of C-shaped casein with a notch and center hole inside that gradually narrowed upon absorbing water. The ameroid constrictors were attached to bilateral ovarian/uterine arteries at the 17th day of pregnancy to induce chronic mild ischemia, which led to FGR with over 20% body weight reduction. After the intravenous administration of 1×105 UC-MSCs, we confirmed a significant improvement in the UC-MSC group in a negative geotaxis test at one week after birth and a rotarod treadmill test at five months old. In the immunobiological evaluation, the total number of neurons counted via the stereological counting method was significantly higher in the UC-MSCs group than in the vehicle treated group. These results indicate that the UC-MSCs exerted a treatment effect for neurological impairment in the FGR rats.